Once Again: The Concept of Wu-Hsing - Friedrich, Michael; Lackner, Michael (Early China, 1985)
First, we should like to point out that the whole debate is obviously based on a narrowly modern conception of “element,” which only covers one tenth of the history of the term. The following passages should help to remedy this regrettable neglect of the broader and chronologically more significant meaning of the concept. They are drawn directly from original sources rather than from works such as Needham's, which has already been overworked for this purpose.<br